1991
DOI: 10.1159/000235448
|View full text |Cite
|
Sign up to set email alerts
|

Ability of Polymorphonuclear Leukocytes to Generate Active Oxygen Species in Children with Bronchial Asthma

Abstract: Airway inflammation with polymorphonuclear leukocytes (PMN) may play an important role in bronchial hyperresponsiveness (BHR). PMN generate superoxide anion (O2––) and other oxygen radicals that can damage lung tissue. We investigated the ability of peripheral PMN of children with bronchial asthma and control subjects to generate O2–– and other active oxygen species using a 2-methyl-6-(p-methoxyphenyl)-3,7-dihydroimidazo[1,2-α]pyrazin-3-one, a highly sensitive and sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
14
0

Year Published

1993
1993
1999
1999

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 15 publications
1
14
0
Order By: Relevance
“…Our results obtained for PMNs in asthma are in agreement with those obtained by KATO et al [22], and NEIJFENS et al [5]. The results of KATO et al [22] suggested that PMNs in asthmatic children, especially those with attacks, generate more ROS than those of healthy subjects, as assessed by a cypridina luciferin analogue enhanced CL.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our results obtained for PMNs in asthma are in agreement with those obtained by KATO et al [22], and NEIJFENS et al [5]. The results of KATO et al [22] suggested that PMNs in asthmatic children, especially those with attacks, generate more ROS than those of healthy subjects, as assessed by a cypridina luciferin analogue enhanced CL.…”
Section: Discussionsupporting
confidence: 92%
“…The results of KATO et al [22] suggested that PMNs in asthmatic children, especially those with attacks, generate more ROS than those of healthy subjects, as assessed by a cypridina luciferin analogue enhanced CL. NEIJFENS et al [5] suggested that the increased generation of ROS in children with asthma might also contribute to causing bronchial hyperresponsiveness (BHR).…”
Section: Discussionmentioning
confidence: 99%
“…A correlation between neutrophil ROM production and bronchial hyperreactivity has been shown both in bronchial asthma [17,19], and in chronic obstructive pulmonary disease [32]. The magnitude of the neutrophil ROM responses has been reported to correlate with the severity of asthma symptoms [19].…”
Section: Discussionmentioning
confidence: 99%
“…A correlation between neutrophil ROM production and bronchial hyperreactivity has been shown both in bronchial asthma [17,19], and in chronic obstructive pulmonary disease [32]. The magnitude of the neutrophil ROM responses has been reported to correlate with the severity of asthma symptoms [19]. The chemiluminescence signal obtained from whole blood is predominantly a function of neutrophil number and function [33], whilst the contribution of monocytes, lymphocytes and thrombocytes has been considered negligible [22,[34][35][36][37].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation